Effectiveness of Different Bonding Agents in Minimally Invasive Cavity Preparations - Niladri Maiti; Abhilasha Bhawalkar; Rozina Hussain Ali; Nallamilli Lalitha Sri Roja; Pratik Agrawal; Anshuman Shetty; Shalini Singh (Wolters Kluwer Medknow Publications, 2024)
Objective: This research is meant to evaluate the effectiveness of different bonding agents in minimally invasive cavity preparations at a tertiary care center. Materials and Methods: A prospective research was conducted involving patients requiring minimally invasive cavity preparations. Patients were randomly assigned to groups based on the bonding agent used. Standardized cavity preparations were performed, and bonding agent application followed manufacturer instructions. Outcome measures included bond strength and marginal adaptation. Data were analyzed using appropriate statistical methods. Results: Bonding Agent A exhibited the highest mean bond strength (25.6 MPa) and superior marginal adaptation (mean score: 4.2) compared to Bonding Agents B and C. These differences were statistically significant (P < 0.001 for bond strength, P < 0.05 for marginal adaptation). Conclusion: Bonding Agent A demonstrated superior performance in achieving durable and esthetically pleasing restorations in minimally invasive cavity preparations. These findings underscore the importance of selecting appropriate bonding agents for conservative dental treatments to optimize treatment outcomes and patient satisfaction.